An Analysis of Intra-Industry Trade between Japan, Malaysia and China - Mohammad Affendy, Arip; Lau, Sim Yee; Satoru, Madono (University of Malaya, 2011)
This paper investigates the bilateral trade pattern between Japan,Malaysia and China (JMC) using the intra-industry trade (IIT) index analysis. Our empirical findings revealed the following. First, China shows a higher degree of IIT relation with Japan vis-à-vis Malaysia. Second, to the extent of whether rapid manufacturing development in China is affecting Malaysia’s export to Japan, our analytical evidence demonstrates that the degree of overlapping exports to Japan by Malaysia and China has increased over time. Although this trend appears to be an indication of increasing competition from China in relation to Malaysia’s products in the Japanese market, our empirical evidence – detailing the degree of product similarity between Malaysia and China using the unit value (UV) measurement – shows that both countries’ exports actually comprise mainly vertically differentiated products or different segments of the market in Japan. Nevertheless, the results also reveal that, compared to Malaysia, China is rapidly increasing its export share in horizontally differentiated products or similar market segments.